Latinum est... et canitur - Luigi Spina (Annali Online dell'Università di Ferrara. Sezione Lettere)
In a previous article, the Author proposed a triple classification about the relationship between Latin literature and modern (or pop) music: 1) singing Latin texts in original; 2) quoting or hinting at Latin texts; 3) singing Latin texts in translation. Now he adds other examples to these typologies and he suggests a fourth one, very useful to teach Latin at school or at the university: translating pop songs in Latin.